A case of autologous thrombofibrin clot use in a patient with post-burn persistent corneal erosion - E. V. Fedoseeva; E. V. Chentsova; N. V. Borovkova; I. N. Ponomarev; A. O. Petrova; Yu. A. Pavlenko (Трансплантология (Москва))
The purpose. Using clinical observation, to study the feasibility of applying a coagulant and to assess its efficacy in the treatment of patients with post-burn erosion of the cornea.Material and methods. The treatment was carried out in the Department of Trauma and Reconstructive Surgery, the Helmholtz Moscow Research Institute of Eye Diseases, Russia. Based on clinical test results, the patient, was diagnosed with post-burn persistent erosion of the cornea with sub-total cornea conjunctivization and: limbal stem cell deficiency (LSCD) in the right eye. The keratoprotective therapy conducted for several months turned ineffective. In order to activate the cornea regeneration process, the erosion site was covered with autologous thrombofibrin clot that had been obtained from the stabilized blood. Following a two-stage centrifugation of patient's stabilized blood, the plasma with the platelets were collected into a round-bottomed test-tube; and the chloride calcium activator was added. The clot was formed in the thermostat at a temperature of 37 С. The patient was given a local anesthesia, and the thrombofibrin clot was placed on the cornea surface and covered with an amniotic membrane. The membrane was fixed with a circular stitch along the limbus of the cornea.Result. The patient was followed-up and showed positive changes over time in the form of a diminished erosion area at day 5 and a complete corneal epithelialization at day 14.Summary. Our methodaimed at enhancing the reparative and regenerative processes in the cornea, reducing swelling, accelerating epithelialization, expanding transparency, and improving the optic characteristics thanks to less intensive opacity formation showed a high efficacy.